SAT0210 Brain magnetic resonance imaging (mri) and proton magnetic resonance spectroscopy (1h-mrs) in systemic lupus erythematosus (sle). (1st June 2001) - Govoni, M; Colamussi, P; Rizzo, N; Santilli, D; Ricci, R; Trotta, F
Abstract : Background: Objectives: We evaluated the usefulness of 1H-MRS in patients with SLE, with or without neurological involvement, in whom single photon emission computed tomography (SPECT) showed cerebral perfusion abnormalities in brain areas with no detectable changes at MRI. Methods: 9 female SLE patients, with a mean age of 28.7 years (range 14–46) and a mean duration of disease of 2.5 years, underwent cerebral blood flow (CBF) study with 99mTc-SPECT and brain MRI with 1H-MRS analysis. 4 patients complained of headache, 1 patient was being treated for partial epilepsy and 4 patients were asymptomatic and with a negative neurological examination. In brain areas shown to be hypoperfused by SPECT, peak levels of signals from brain metabolites N-acetylaspartic acid (NAA), choline (CHO), and creatine (CRE) were measured on a total of 20 brain voxels (volume = 8 cm 3 ) selected on transverse MR images. Values were expressed as NAA/CHO, CHO/CRE and NAA/CRE ratios. Ratios measured in 9 hypoperfused brain areas were compared with those obtained in 11 normoperfused areas. MRI showed a normal appearance in all of the above brain areas. Statistical analysis was performed by means of classical t-test. Results: NAA/CHO ratio was decreased in 78% of hypoperfused and in 18% of normoperfused brain areas (1.70 ± 0.15 vs 2.55 ± 0.16; p = 0.0017). CHO/CRE ratio was increased in 89% of hypoperfused and in 9% of normoperfused brain areas (1.34 ± 0.08 vs 0.80 ± 0.05; p < 0.0001). No significant differences were detected in NAA/CRE ratios. The comparison of spectroscopic ratios measured both in hypoperfused and normoperfused areas in patients with neurological symptoms with those obtained in asymptomatic patients did not show any significant differences. Conclusion: In SLE patients, independently from the presence of overt clinical neurological involvement, 1H-MRS is a valuable tool to detect neuronal biochemical changes in brain regions with reduced CBF at SPECT. Although the precise meaning of these abnormalities remains to be determined, their localization in areas with reduced CBF suggests that they could represent an early sign of neuronal injury in SLE patients even in the presence of a normal brain MRI appearance. If proven so, 1H-MRS could be considered a sensitive and accurate measure of neuronal dysfunction in SLE and this would demonstrate that the detection of reduced CBF by SPECT in areas with a normal MRI appearance is not to be regarded as a false positive result.